Tackling the Problem of Sensing Commonly Abused Drugs Through Nanomaterials and (Bio)Recognition Approaches - Truta, Florina; Florea, Anca; Cernat, Andreea; Tertis, Mihaela; Hosu, Oana; de Wael, Karolien; Cristea, Cecilia (Frontiers in Chemistry, 2020)
We summarize herein the literature in the last decade, involving the use of nanomaterials and and varius biorecognition elementsbiomimetic elements, such as aptamers and molecularly imprinted polymers, for the development of sensitive and selective (bio)sensors for illicit drugs with a focus on electrochemical transduction systems. Illicit drugs use and abuse remains an increasing challenge for worldwide authorities and, therefore, it is important to have accurate methods to detect them in seized samples, biological fluids and wastewaters. They are recently classified as the latest group of ‘emerging pollutants’, as their consumption increased tremendously in recent years. Nanomaterials, and biomimetic platforms (e.g. aptamers, molecularly imprinted polymers) have gained much attention over the last decade in the development of (bio)sensors for a myriad of applications. The applicability of these (nano)materials, functionalized or not, significantly increases and are therefore highly suitable for use in the detection of drugs of abuse. Lately, such functionalized nanoscale materials have assisted in the detection of illicit drugs fingerprints, providing large surface area, functional groups and unique properties that facilitate sensitive and selective sensing. The review discusses about the types of drugs of abuse and their toxicological implications, classification of functionalized nanomaterials (graphene, carbon nanotubes), their fabrication, and their application on real samples in different fields of forensic science. Biosensors for drugs of abuse from the last decade’s literature are then exemplified. It also offers insights into the prospects and challenges of bringing the functionalized nano- or/and biomimetic-based technology to the end user in the laboratories or in-field.